If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(8+n)=-3(2n-4)
We move all terms to the left:
-(8+n)-(-3(2n-4))=0
We add all the numbers together, and all the variables
-(n+8)-(-3(2n-4))=0
We get rid of parentheses
-n-(-3(2n-4))-8=0
We calculate terms in parentheses: -(-3(2n-4)), so:We add all the numbers together, and all the variables
-3(2n-4)
We multiply parentheses
-6n+12
Back to the equation:
-(-6n+12)
-1n-(-6n+12)-8=0
We get rid of parentheses
-1n+6n-12-8=0
We add all the numbers together, and all the variables
5n-20=0
We move all terms containing n to the left, all other terms to the right
5n=20
n=20/5
n=4
| (x)(x-2)=323 | | -1/2+r=7/2 | | 2/3r+1/2=7/8 | | 5(c-73)=75 | | x/13=5/17 | | 10-2u=-10-6u | | 144+2h=992 | | 36-c=42 | | O=3x-x | | y=6-1+(-2) | | 8x-3-5x=2x | | -4p+23=11 | | 10r-3=9r-6-5 | | 5(2w-3)+10=3w+16 | | 3(7x+5)=2x-9 | | 12+2h=992 | | 6x-2=19=3x | | C=40/3x+20,R=15x | | 3(x+4)=2x-4 | | y+(-14)=-13 | | −1+x=4 | | -6b-3=-2b+9 | | 6=n/4+4 | | 6g+17=71 | | 42c=36 | | -10-5p+9=9-6p | | 36+c=42 | | -10-2s=4s+8 | | -8/3x+1=13/3+2/3x | | x+19=5x+17 | | 82(2x+8)=28(5x-4) | | f(70)=4(70)-2 |